2009
DOI: 10.1017/s0950268809990641
|View full text |Cite
|
Sign up to set email alerts
|

Dirty hands: bacteria of faecal origin on commuters' hands

Abstract: SUMMARYAlthough many studies have investigated bacteria on the hands of health-care workers and caregivers, few have looked at microbiological contamination on the hands of the general adult public. This study investigated faecal bacteria on the hands of commuters in five UK cities. Of the 404 people sampled 28% were found to have bacteria of faecal origin on their hands. A breakdown by city showed that the proportion of people with contaminated hands increased the further north the city of investigation (P<0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
1
28
0
1
Order By: Relevance
“…Recently Judah et al could demonstrate that 28% of the general adult population have bacteria of faecal origin on their hands in the UK. 13 This indicates the importance of hands as routes of transmission of bacteria not only of potential faecal origin but also of multi-resistant pathogens in the broad population and emphasises the development of new techniques for efficient inactivation of such pathogens. Recently photodynamic treatment of microorganisms has been shown to be very effective in vitro as well as in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Judah et al could demonstrate that 28% of the general adult population have bacteria of faecal origin on their hands in the UK. 13 This indicates the importance of hands as routes of transmission of bacteria not only of potential faecal origin but also of multi-resistant pathogens in the broad population and emphasises the development of new techniques for efficient inactivation of such pathogens. Recently photodynamic treatment of microorganisms has been shown to be very effective in vitro as well as in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were tested for E. coli and Enterococcus , because these are thought to indicate faecal origin of finger contamination, and were therefore used in previous work [7,17,18,19,20,21]. To minimise the laboratory work and the need for microbiological expertise we used the CPS3 chromogenic agar (BioMerieux, Marcy l’Etoile, France) which allows identification of E. coli and Enterococcus spp.…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous studies examining handwashing and bacteria residing on the hands of healthcare workers (1,160,000 research citations in Google Scholar using handwashing and health care as keywords). As a survey of the general public, Judah et al (2010) [7] examined the hands of commuters in five UK cities and reported that 28% carried bacteria of fecal origin. Interestingly, in this same study, bus commuters had higher fecal bacteria counts than train riders.…”
Section: Introductionmentioning
confidence: 99%